Fostering food preservation practice: Lessons from a community train-the-trainer program on Canada's west coast - Oloko, Majing; Reed, Maureen G.; Robson, James P. (Frontiers in Sustainable Food Systems, 2022)
Local food systems programs in Canada's rural and remote communities support residents to improve their access to healthy food by strengthening various social practices within the system. Designing programs to strengthen social practices can help address food insecurity by providing a support structure where people can build competencies and access materials necessary to engage in practices like food preservation, and make meanings that will encourage them to sustain their engagement. The elements needed for successfully establishing a social practice – competencies, materials, and meanings – must be present. Unfortunately, food preservation programs in Canada's local food systems have not fully embedded structures to bring all three elements of social practice together or undertake a participant-focused program assessment. Consequently, we do not know the potential of local food preservation to meet peoples' various needs or the challenges that program participants experience practicing food preservation. This paper uses a social practice framework to determine the extent to which a community food preservation program on Canada's west coast strengthened the three elements of social practice. Findings from interviews show that in line with the paper's three objectives, participants of a community train-the-trainer program 1) built and shared food preservation competencies, 2) accessed materials to practice food preservation, and 3) formed meanings to support their continuous engagement in food preservation. The paper shows how a social practice framework can support a participant-focused program evaluation and provide a practical and straightforward tool for assessing food systems programs.